2020
DOI: 10.3389/fnbeh.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Binge-Like, Naloxone-Sensitive, Voluntary Ethanol Intake at Adolescence Is Greater Than at Adulthood, but Does Not Exacerbate Subsequent Two-Bottle Choice Drinking

Abstract: The present study assessed the effects of ethanol exposure during adolescence or adulthood. We exposed Wistar rats, males or females, to self-administered 8-10% (v/v) ethanol (BINGE group) during the first 2 h of the dark cycle, three times a week (Monday, Wednesday, and Friday) during postnatal days (PDs) 32-54 or 72-94 (adolescent and adults, respectively). During this period, controls were only handled, and a third (IP) condition was given ethanol intraperitoneal administrations, three times a week (Monday,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 69 publications
5
12
2
Order By: Relevance
“…In the present work, we exposed mice to intermittent air or ethanol exposure at the same age during adolescence and the length of abstinence was varied to allow us to understand the impact of short-term and protracted abstinence on subsequent ethanol consumption and open field behavior. This is similar to recent work that used a DID exposure paradigm and varied the withdrawal period to assess changes in ethanol consumption and anxiety-like behavior (Jimenez Chavez et al, 2020;Salguero et al, 2020). Specifically, we exposed adolescent (PND 28-42) C57BL/6J mice to adolescent intermittent ethanol (AIE) vapor exposure and measured voluntary ethanol intake (a) 1 week following the initial exposure while the mice were still adolescents and (b) 4 weeks following the AIE exposure when the mice were emerging adults.…”
Section: Significancesupporting
confidence: 79%
“…In the present work, we exposed mice to intermittent air or ethanol exposure at the same age during adolescence and the length of abstinence was varied to allow us to understand the impact of short-term and protracted abstinence on subsequent ethanol consumption and open field behavior. This is similar to recent work that used a DID exposure paradigm and varied the withdrawal period to assess changes in ethanol consumption and anxiety-like behavior (Jimenez Chavez et al, 2020;Salguero et al, 2020). Specifically, we exposed adolescent (PND 28-42) C57BL/6J mice to adolescent intermittent ethanol (AIE) vapor exposure and measured voluntary ethanol intake (a) 1 week following the initial exposure while the mice were still adolescents and (b) 4 weeks following the AIE exposure when the mice were emerging adults.…”
Section: Significancesupporting
confidence: 79%
“…AAE has also been reported to promote alcohol consumption in adult rats, 11,36,39,47,48 although opposite results have been reported 53,54 . In the present study, voluntary adolescent binge‐drinking promoted alcohol consumption and preference in adult males and females but not in adolescents.…”
Section: Discussioncontrasting
confidence: 61%
“…A large body of evidence supports the mediating role of opioid receptors on ethanol intake, and the antagonism of this system is a common therapeutic target on AUD treatment. 24,25,29 Recent studies have reported a similar role of opioid receptors antagonism on BE as well. 30 Furthermore, both ethanol intake and BE have been reduced by modulating other pharmacological targets such as corticotropin-releasing factor, 31,32 dopamine receptors 33,34 and sigma-1 receptor, 35,36 which support the connection between the two behaviours.…”
Section: Discussionmentioning
confidence: 92%